THE CONCEPT OF ISLAMIC EDUCATION IN THE ERA OF GLOBALIZATION (A COMPARATIVE STUDY OF THE PERSPECTIVES OF SYED NAQUIB AL ATTAS AND KH. ABDURRAHMAN WAHID) - Fikri Fathul Aziz; Fahri Fathur Rohman; Irfan Maulana Adnan (Yayasan Haiah Nusratul Islam, 2025)
The era of globalization has significantly impacted various aspects of life, including the Islamic education system. The rapid pace of modernization and technological advancement necessitates a renewal of educational approaches that remain rooted in Islamic values. This study aims to comparatively examine the concept of Islamic education from the perspectives of two prominent figures, Syed Muhammad Naquib al-Attas and KH. Abdurrahman Wahid, in responding to the challenges of globalization while preserving Islamic and national identity. This research employs a qualitative method through a library research approach, using content analysis of the major works of both thinkers. Al-Attas emphasizes education as a process of Islamization of knowledge and the cultivation of adab (ethical discipline), whereas Wahid focuses on the importance of inclusivity, pluralism, and openness to global thought while upholding Islamic principles. Their differing backgrounds and intellectual orientations offer unique frameworks in formulating an Islamic education system relevant to contemporary contexts. The findings reveal that despite methodological and philosophical differences, both figures share the view that Islamic education serves as a means of social and moral transformation. Al-Attas’s concept is more normative and philosophical, while Wahid’s ideas are practical and contextual. These insights suggest that synthesizing both perspectives could provide a strategic foundation for developing an Islamic education system that is both adaptive to global challenges and faithful to spiritual and cultural Islamic values.